Evaluation of disinfection methods of orthodontic pliers - Almeida,Camilla Machado Feitosa de (2012)
INTRODUCTION: In recent years, a strong behavior change regarding the control of cross infection during dental treatment was perceived, except among some orthodontists who insist in the misconception that Orthodontics is a specialty of low risk in the transmission of infectious and contagious diseases. OBJECTIVE: The objective of this study was to evaluate the methods used by orthodontists for disinfection of pliers in their daily practice. METHODS: The bacteria Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus salivarius were inoculated in vitro in 30 orthodontic pliers. The pliers were divided into 3 groups (n = 10) and disinfected in different ways. Group 1: Brush, soap and water; Group 2: Cotton soaked in ethyl alcohol 70%; Group 3: Immersion in a solution of 2% glutaraldehyde for 30 minutes and then rinsed with water. RESULTS: The results showed that the ethyl alcohol 70% (Group 2) kept 20% of the pliers infected, being more efficient than the soap and water (Group 1), which maintained 60% of contaminated pliers. Only immersion in 2% glutaraldehyde was able to decontaminate all pliers and was statistically superior to the aforementioned methods (p = 0.030). CONCLUSION: Based on these results, we concluded that among the tested methods, disinfection of orthodontic pliers with 2% glutaraldehyde is the only efficient method.